Recovery of neurological function following type B aortic dissection complicated by paraplegia. Issue 4 (22nd April 2022) - Li, Ben; Khoshhal, Zeyad; Common, Andrew; Qadura, Mohammad
Abstract : A woman in her 50s presented with uncontrolled hypertension, chest/back pain, paraplegia, right lower limb ischaemia and acute kidney injury. A CT angiogram demonstrated a type B aortic dissection originating distal to the left subclavian artery to bilateral common iliac arteries complicated by occlusion of the right renal artery and right common iliac artery. She was started on intravenous antihypertensive therapy and transferred to our institution for emergent thoracic endovascular aortic repair. Due to bleeding risk from coagulopathy, a spinal drain was not placed immediately post-operatively but instead was inserted after 24 hours while maintaining a mean arterial pressure of 80–100 mm Hg. Postoperatively, her right lower extremity perfusion was re-established, and her renal function recovered following temporary dialysis. At discharge on postoperative day 13, she regained full neurological function.